PEMENUHAN UNSUR-UNSUR TINDAK PIDANA MENGHASUT ORANG LAIN DALAM AKSI UNJUK RASA ANARKIS OLEH PENYIDIK SATUAN RESERSE KRIMINAL KEPOLISIAN RESOR AGAM - Muzhendra Muzhendra; Iyah Faniyah; Adhi Wibowo (UNES Journal of Swara Justisia, 2019)
The offense of incitement is regulated in Article 160 and Article 161 paragraph (1) of the Criminal Code as an act whose offensive is directed to public order in which the regulation of this criminal act is intended to protect the legal interest of public order. The occurrence of an anarchist rally originated from the incitement of the suspect by inciting the masses, so that the words and sentences made by the suspect at the time of the mass rally became brutal and anarchic. Against the instigating action that resulted in anarchism, the mass of the investigator requested responsibility through the investigation process by applying the elements of the provision so that it could be qualified as a criminal act to incite others.